2021
DOI: 10.3390/jcm10081665
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer Exposome Profile to Aid Early Detection and Inform Prevention Strategies

Abstract: Pancreatic cancer (PCa) is associated with a poor prognosis and high mortality rate. The causes of PCa are not fully elucidated yet, although certain exposome factors have been identified. The exposome is defined as the sum of all environmental factors influencing the occurrence of a disease during a life span. The development of an exposome approach for PCa has the potential to discover new disease-associated factors to better understand the carcinogenesis of PCa and help with early detection strategies. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 232 publications
(179 reference statements)
0
8
0
Order By: Relevance
“…However, there are not always satisfactory for HCC targeted therapies in partial patients due to the differences of their clinicopathological features and genes (20). For example, it is well known that alcohol consumption is a risk factor for HCC and other cancers (21)(22)(23)(24)(25), but there are still many unknown molecular mechanisms and prognostic biomarkers in alcoholrelated HCC. Therefore, prognostic biomarkers with higher prediction accuracy in predicting prognosis are urgently needed before detectable clinicopathological abnormalities in treatments of alcohol-related HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are not always satisfactory for HCC targeted therapies in partial patients due to the differences of their clinicopathological features and genes (20). For example, it is well known that alcohol consumption is a risk factor for HCC and other cancers (21)(22)(23)(24)(25), but there are still many unknown molecular mechanisms and prognostic biomarkers in alcoholrelated HCC. Therefore, prognostic biomarkers with higher prediction accuracy in predicting prognosis are urgently needed before detectable clinicopathological abnormalities in treatments of alcohol-related HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review by Gracia-Cazaña et al 37 suggested that physical–chemical substances, living entities (such as polyomavirus and human papillomavirus), and lifestyle factors made up the exposome of skin cancer, and this set of environmental exposures could determine the incidence of skin cancer. One study on pancreatic cancer (PCa) used the exposome approach to extract variables from general external, internal external, and specific external domains 38 . This study identified that several exposome factors were related to PCa alone and in combination with other exposures.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Pancreatic cancer often accompanies with distant metastasis and generally shows poor prognosis [ 3 6 ]. Pancreatic cancer remains one of the most lethal malignancies with a 5-year survival rate of 5–10% [ 7 , 8 ]. Pancreatic cancer is often already incurable at the time of diagnosis and have a median overall survival of 6–12 months even with palliative chemotherapy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer remains one of the most lethal malignancies with a 5-year survival rate of 5–10% [ 7 , 8 ]. Pancreatic cancer is often already incurable at the time of diagnosis and have a median overall survival of 6–12 months even with palliative chemotherapy [ 7 ]. The risk of postoperative recurrence is high, and a 5-year survival rate after surgery was documented as approximately 30% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation